Palm Oil Mill Effluent Treatment Technology using Sequencing Batch Reactor (SBR) with Oxidation Reduction Potential (ORP) Monitoring - Sanjaya, Andri; Saputri, Desi Riana; Damayanti, Damayanti; Fahni, Yunita; Auriyani, Wika Atro; Mustafa, Mustafa (Jurnal Teknik Kimia dan Lingkungan, 2024)
Palm oil industries have products like Crude Palm Oil (CPO), and 70% of others contain waste. One of the wastes is the liquid waste known as Palm Oil Mill Effluent (POME). The potential of POME to be reprocessed into clean water will be profitable. One of POME's reprocessing methods is the Sequencing Batch Reactor with Aerobic Granulated Sludge (SBR-AGS), which has five main phases: filling, idling, aeration, settling, and discharge, with a cycle time of 360 minutes. The first step in using this reactor is the start-up process, a granule-forming process from some sludge that has already acclimatized. In one complete cycle, the Oxidation-Reduction Potential (ORP) parameter is used to observe the electron transfer process that shows the oxygen supply into the reactor, which enables the condition of each phase in the process to be analyzed. The trend of ORP value is constantly changing in every phase. For the idling phase, the ORP tends to decrease in a value of (-300)-(-400) mV, and for the aeration phase, it will increase in a value of (-100)-100 mV.